PENGARUH KEEFEKTIFAN PENGENDALIAN INTERNAL, KETAATAN ATURAN AKUNTANSI DAN KESESUAIAN KOMPENSASI TERHADAP KECURANGAN (FRAUD) AKUNTANSI PADA ORGANISASI PERANGKAT DAERAH (OPD) KABUPATEN KUTAI TIMUR - Lewi Patabang; Rahmawati Fitriana; Fatmawati Nurhaliza (Jurnal Eksis, 2021)
The aims of this research are to know the influence of Effect of Internal Control Effectiveness, Observance of the rules accounting and compliance compensation on accounting fraud. The object of research in this study is Local Government Institution (OPD) of East Kutai Regency. Pursuant to Accedential Sampling method, total sample in this research is 71 responden from 3 Local Government Institution (OPD) of East Kutai Regency. Hypothesis in this research use meltiole linear regression analysis. The results of this study are: (1) There is no significant effect between the Effectiveness of Internal Control on Accounting Fraud in OPD East Kutai Regency, this is indicated by the tcount value of the Internal Control Effectiveness variable of 0.238 <from the ttable value of 1.668 and the significance value in the table of 0.812 (above 0.05). (2) There is a negative and significant influence between the Compliance of Accounting Rules on Accounting Fraud, this is indicated by the tcount value of the Accounting Rules Compliance variable of -2.336> of the t table value of 1.668 and the significance value of the table of 0.023 (below 0.05). (3) There is no significant effect between Compensation Suitability for Accounting Fraud in OPD East Kutai Regency, this is indicated by the tcount of the Compensation Suitability variable of 0.744 <from the ttable value of 1.668 and the significance value in the table of 0.459 (above 0.05 ). (4) There is no significant influence between the Effectiveness of Internal Control, Compliance with Accounting Rules and Compensation Compensation for Accounting Fraud in OPD East Kutai Regency, this is indicated by the Fcount value of 2.071 <from the t-table value of 2.74 and the significance value in the table of 0.112. (above 0.05).Keywords : effectiveness of internal control. Observance of the rules accounting, compliance compensation of acoounting fraud.